CONCEPTUALISING SOUNDSCAPE PREFERENCE IN HIGH-TRAFFIC COMMERCIAL STREETS - Mat Ghazi, Muhammad Afif Abidi; Abdul Hamid, Nor Hamizah (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
Conventional noise management approach in urban contexts primarily prioritised decibel reduction. This approach neglects human perception and experience of sound, particularly in complex settings like high-traffic commercial streets. While prior soundscape studies have comprehensively covered public open areas such as urban squares and urban parks, there remains a gap in understanding acoustic experiences on high-traffic commercial streets. This study addresses this gap by developing a soundscape conceptual framework for high-traffic commercial streets. The study synthesises key findings from a narrative of literature published between 2016 and 2026 to identify the factors of soundscape preference. The proposed framework posits context (environmental and personal factors) and sound sources as independent variables that influence auditory sensation and shape soundscape preference. Soundscape preference is conceptualised as a multi-faceted variable that includes soundscape descriptors and the preferred sounds. This approach shifts from typical decibel reduction to utilisation of various sounds, where sounds are treated as resources to improve the acoustic comfort for psychological well-being. The conceptual framework offers guidelines for urban designers to integrate the soundscape approach into urban design. Urban designers can incorporate elements that promote preferred sounds and minimise unwanted ones, based on the contextual and acoustic factors, to create an acoustically pleasant space.